Solar Power System for Flexitank Electrical Heating Pad - Nurul Asyiqin,; Puteri Najwa Aida Elieyana ,; Dr Nor Shahida ,; En Omar, (Progress in Engineering Application and Technology, 2023)
Generally, a steamed powered heating pad is used to heat up liquid products in a flextitank. However, it takes time for the liquid to melt and melting is only done when destination is reached. The aim of this project is to design and implement a solar power system for electrical heating pad. This will save more time as the liquid can be heated continuously through the journey. A solar charge controller is used to control the voltage from the solar panel and allow the required voltage needed to power the heating element. In this project, a 12 V heating pad is used as the heating element and the system is tested to heat a 12x12 cm dimension of LLDPE. A 12 V battery is used as storage and can be used as a power supply during night transportation or when there is no sunlight.